ANALISIS LAPORAN KEUANGAN SEBAGAI DASAR DALAM PENILAIAN KINERJA KEUANGAN SPBU SAYATI 34-40251 - Mira Anggraena; Meri Anggraeni; Resmi Ranti Rosalina (Journal of Economic, Bussines and Accounting (COSTING), 2023)
The purpose of thus study is to identify changes in the company's financial condition and operating performance over several periods, provide management insights and projections regarding the growth and decline of the company's financial condition in the future. This research method uses descriptive quantitative method. Four significant figures are used when analyzing the financial statements of the Sayati gas station 34-40251: liquidity ratio, solvency ratio, profitability ratio and activity ratio. Based on our research and analysis of the financial statements for the period 2017 to 2020, the financial performance of the Sayati 34-40251 gas station is liquid and stable because it can fulfill all its obligations, can earn income from all its activities, can use company resources efficiently despite a decline in financial performance. in 2020 due to the spread of Covid 19, but this did not have a negative impact on business operations. Keywords : Ratio Liquidity, Ratio Solvability, Ratio Profitabilitas, Ratio Activity, Financial Report